2020
DOI: 10.3390/jcm9082480
|View full text |Cite
|
Sign up to set email alerts
|

Translating Evidence from Clonal Hematopoiesis to Cardiovascular Disease: A Systematic Review

Abstract: Some random mutations can confer a selective advantage to a hematopoietic stem cell. As a result, mutated hematopoietic stem cells can give rise to a significant proportion of mutated clones of blood cells. This event is known as “clonal hematopoiesis.” Clonal hematopoiesis is closely associated with age, and carriers show an increased risk of developing blood cancers. Clonal hematopoiesis of indeterminate potential is defined by the presence of clones carrying a mutation associated with a blood neoplasm witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 101 publications
1
13
0
1
Order By: Relevance
“…It is now well established that the incidence of CVDs increases with aging [ 17 , 65 ], although the majority of elderly patients suffering from CVD have either no conventional risk factor or just one risk factor [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that the incidence of CVDs increases with aging [ 17 , 65 ], although the majority of elderly patients suffering from CVD have either no conventional risk factor or just one risk factor [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that shear stress and vascular remodeling played a crucial role in the benefits of exercise in CVD. Atherosclerosis and inflammation seem to be the cross-talking pathways between the two diseases [ 17 ], the shear stress and the remodeling of vascular endothelium being the common process both in CVD and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were also presented when a subclonal population potentially indicating clonal hematopoiesis of indeterminate potential (CHIP) [25] was observed. CHIP, a recently described entity, is sometimes incidentally detected by NGS tests and can be a precursor to hematologic malignancies and cardiovascular disease [26]. Individuals in whom CHIP was identified (n = 5, 3%) and discussed in MTB have been referred to a CHIP clinic recently begun at Vanderbilt University Medical Center.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, inflammatory signaling is one of the key mechanisms by which CHIP with somatic mutations such as TET2/DNMT3A increases risk of cardiovascular events. Likely, TET2/DNMT3A mutations increase proinflammatory cytokine release, driving a feedback loop that leads to clonal expansions of mutant dominant cells, which then again amplifies deregulated and unbalanced release of pro-inflammatory cytokines [61]. Whether other CHIPrelated mutations also increase cardiovascular risk through inflammatory mechanisms is not clear.…”
Section: Inflammatory Pathways Involved In the Mechanism By Which Chip Increases Cardiovascular Riskmentioning
confidence: 99%